PENILAIAN SENSORI FLAKES TEPUNG BONGGOL PISANG DENGAN PENAMBAHAN TEPUNG TEMPE - Kepri Dianto; Vonny Setiaries Johan; Rahmayuni Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this research was obtained the best and ratio of tuber banana flour and tempeh flour in flakes making. These research used to Completely Randomized Design (CRD) with five treatments and three replications, followed by DNMRT test at 5% level. The treatment for this research were BT1 (tuber banana flour 80 g), BT2 (tuber banana flour 75 g + tempeh flour 5 g), BT3 (tuber banana flour 70 g + tempeh flour 10 g),BT4 (tuber banana flour 65 g + tempeh flour 15 g), BT5 (tuber banana flour 60 g + tempeh flour 20 g). Analysis of flakes light brown in color, texture were  a bit hard without milk adding and soft with the addition of milk, slightly scented tuber banana flour and tempeh flour, and slightly taste tuber banana flour and tempeh flour.  Keywords: Flakes, tuber banana flour, tempeh flour.